Quality assessment of the physicochemical properties of vermiwash produced from different sources during successive storage periods - JAIKISHUN, SIRPAUL; ADONIS, SHAMIKA; ANSARI, ABDULLAH ADIL (Asian Journal of Agriculture, 2018)
Abstract. Jaikishun S, Adonis S, Ansari AA. 2018. Quality assessment of the physicochemical properties of vermiwash produced from different sources during successive storage periods. Asian J Agric 2: 52-57. Organic farming is crucial for maintaining our health together with improving quality and quantity of crop production in environmentally friendly farming practices. Vermiwash is poised to be one of the key components in organic farming and reducing the enormous amounts of pollutants from the environment. This study aims to determine the physicochemical characteristics related to vermiwash from different sources (Jamun, Neem and Grass with combination and mixed with cattle dung) during a three-month storage period with monthly assessments and compared to fresh sample. While an increase in Electrical Conductivity (EC) was seen at the first month, successive decreases were noted thereafter with a significant difference (p=0.05) being observed among the treatments (p=0.05) after three months. Total dissolved salts decreased over the storage period with significant difference being observed among the treatments and storage period revealed that at p=0.05, F (7, 21) = 3.9>2.49 Fcrit. and F (3, 21) = 3.8>2.49 respectively. Phosphorous decreased while potassium increased with T7 having the highest. Calcium showed a significant difference (p=0.05) among the treatments while magnesium fluctuated during the period but deceased at the end of the storage period. Analysis of ferrous content revealed a significant difference (p=0.05, F (7, 21) = 3.8>2.48 Fcrit.) with the time period being significantly different (p=0.05, F (3, 21) = 6.8>3.0) with an increase at the end of the storage period. Fresh form of vermiwash is best to use to obtain maximum nutrients as the general nutrient composition deteriorates over with time